Using Discovery Learning to Improve Students’ Chemical Problem-Solving Skills - M. Mahfudz Fauzi Syamsuri; Indah Tri Rahmadhani; Ila Rosilawati (IJCER (International Journal of Chemistry Education Research), 2023)
This study aims to describe the effectiveness of discovery learning on electrolyte and non-electrolyte solution materials to improve problem-solving skills. This research was conducted at YP Unila Bandar Lampung High School by using the Pretest-Posttest Control Group design. The results showed that the average n-gain in the experimental and control classes were 0.68 (medium category) and 0.45 (medium category), respectively. Based on statistical test results there are differences in the average n-gain, so it can be said that discovery learning on electrolyte and nonelectrolyte solution material is effective in improving problem-solving skills